A New Method for Manufacturing Depleted Uranium Dioxide (DUO2) Material for Spent Nuclear Fuel - Moh. Hardiyanto (JURNAL ILMU PENGETAHUAN DAN TEKNOLOGI (IPTEK), 2014)
Cermets (ceramics embedded in a metal matrix) using depleted uranium dioxide (DUO2) and other ceramics embedded in a steel matrix are being investigated as materials of construction for (1) spent nuclear fuel (SNF) storage, transport, disposal, and multifunction casks and (2) casks for gamma-emitting radioactive wastes. Cermets cask performance (capacity for a given weight limit, capacity for a given size limit, resistance to assault, etc.) may significantly exceed the performance of casks constructed of more traditional materials such as steel. The principal viability issue is manufacturing costs. A new powder metallurgy method for fabricating large casks has been invented (patents applied for) that may result in low fabrication costs. Its potentially favorable economics are a result of (1) a process that produces a near-final-form cask with a minimum number of processing steps and (2) the low cost of the starting materials.